2018
DOI: 10.1371/journal.pone.0204553
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacokinetics of intramuscular alfaxalone and its echocardiographic, cardiopulmonary and sedative effects in healthy dogs

Abstract: The pharmacokinetics and the effects of a single intramuscular (IM) dose of alfaxalone on sedation and cardiopulmonary and echocardiographic variables was studied in dogs. Twelve healthy adult Beagles (3 females, 9 males) were used in this prospective controlled cross-over trial. Echocardiography was performed with and without 4 mg kg-1 alfaxalone IM with a week wash-out interval. Sedation (19-point scale; 0 = no sedation), cardiopulmonary parameters, blood gas analysis and plasma concentration of alfaxalone w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

4
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 31 publications
4
27
0
Order By: Relevance
“…In the ALF group, the level of SpO 2 remained > 90%, similar to that observed in previous studies [ 27 , 32 ]. The XYL-ALF group showed a decrease SpO 2 with mean values varying from 82% to 87% for 25 min post-induction; however, no significant clinical signs of cyanosis were observed.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In the ALF group, the level of SpO 2 remained > 90%, similar to that observed in previous studies [ 27 , 32 ]. The XYL-ALF group showed a decrease SpO 2 with mean values varying from 82% to 87% for 25 min post-induction; however, no significant clinical signs of cyanosis were observed.…”
Section: Discussionsupporting
confidence: 90%
“…These findings were similar to those observed in previous studies in sheep [ 6 , 7 ]; however, in the XYL-ALF group, SAP and MAP were decreased but remained within the clinically acceptable range. In this study, the stability of arterial blood pressures suggested that increased HR was not a baroreceptor response to hypotension, as previously reported [ 30 , 32 ]. However, it was hypothesized that increased HR acts as a compensatory reflex to maintain CO within the normal range [ 29 , 33 ].…”
Section: Discussionsupporting
confidence: 86%
“…Finally, alfaxalone gets benefits from its high safety, its fast clearance, and short half-life, following the quick hepatic metabolism by esterases and the very efficient renal excretion, without massive accumulations in body tissues [34,35]. Nevertheless, at term of pregnancy, the maternal hemodynamic status undergoes a physiological overload due to gestation itself, especially in giant-size dogs [52,53,54], and the low cardio-circulatory impact of alfaxalone at standard dosages (up to 3 mg/kg) [55] on the maternal side is of paramount advantage.…”
Section: Discussionmentioning
confidence: 99%
“…Tamura et al [ 24 ] reported that hypoxemia associated with a decrease in RR was observed in a dose-dependent manner following the IM administration of 5, 7.5, and 10 mg/kg alfaxalone, while the cardiovascular status was well-maintained. In contrast, Maney [ 13 ] reported that low IM doses of alfaxalone alone at 1 and 2 mg/kg produced no change in RR in dogs, and Cruz-Benedetti et al [ 1 ] reported that there were no significant changes in oxygenation even though the RR decreased significantly in dogs that received 4 mg/kg alfaxalone IM. Lee et al [ 11 ] reported that a combination of 10 µg/kg medetomidine, 0.1 mg/kg butorphanol, and 1.5 mg/kg alfaxalone caused severe hypoxemia associated with a decrease in RR in healthy dogs.…”
Section: Discussionmentioning
confidence: 99%